Pemanfaatan Sosial Media Youtube dalam Pembelajaran Menulis pada Masa Sekolah Tatap Muka di SMP Negeri 38 Palembang - Kardika, Rizky Widia; Subyantoro, Subyantoro; Pristiwati, Rahayu (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
The purpose of this study was to describe the teacher's steps in using YouTube social media in learning to write during face-to-face schooling and describe the advantages and disadvantages of using YouTube social media in teaching writing during face-to-face schooling at SMP Negeri 38 Palembang. This research method uses field research with a qualitative approach. Data collection was obtained through observation and interview methods. Based on the results of data analysis carried out by the teacher's steps in utilizing YouTube social media in learning to write during the face-to-face school period at SMP Negeri 38 Palembang, it is applied with reference to the lesson plan used by the teacher with a constructivism approach through 3 stages, namely introduction, core activities, and Closing. The results of this study indicate that the use of videos in YouTube media can stimulate creativity, interest, and motivation from students. In addition, through the YouTube media, students and teachers carry out the following activities: (1) In utilizing YouTube social media, the teacher will first upload videos related to writing material to YouTube and add schedules, video descriptions, and share links to make it easier for students to access the videos. Indonesian language learning; (2) students will watch writing learning materials in YouTube videos that have been given by the teacher; and (3) students will develop the main idea from the video they have watched and create it in written form.